Universal School-Based Implementation of Screening Brief Intervention and Referral to Treatment to Reduce and Prevent Alcohol, Marijuana, Tobacco, and Other Drug Use: Process and Feasibility - Julie Maslowsky; Julie Whelan Capell; D Paul Moberg; Richard L Brown (SAGE Publishing, 2017)
Screening, Brief Intervention, and Referral to Treatment (SBIRT) is an evidence-based approach to reducing substance use in adolescents. An emerging literature shows the promise of school-based SBIRT. However, most school-based SBIRT has only targeted substance-using adolescents and used school-based health clinics, which most schools lack. This project aimed to describe the following: a model for implementing universal SBIRT in high schools without school-based clinics, reasons students most commonly endorsed for reducing or avoiding substance use, students' perceptions of SBIRT, and students' intentions to change substance use or remain abstinent following SBIRT. Participants were N = 2513, 9th to 10th grade students in 10 high schools. Students rated SBIRT positively and indicated substantial intentions to reduce or delay substance use following SBIRT. Results support SBIRT's potential to delay substance use among current abstainers in addition to reducing substance use among current users. This project demonstrates SBIRT's feasibility as a universal method in high schools without in-school clinics.